2001
DOI: 10.1159/000054045
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Potential HIV-Induced Source of Bystander-Mediated Apoptosis in T Cells: Upregulation of TRAIL in Primary Human Macrophages by HIV-1 Tat

Abstract: The induction of apoptosis in T cells by bystander cells has been repeatedly implicated as a mechanism contributing to the T cell depletion seen in HIV infection. It has been shown that apoptosis could be induced in T cells from asymptomatic HIV-infected individuals in a Fas-independent, TNF-related apoptosis-inducing ligand (TRAIL)-dependent manner if the cells were pretreated with anti-CD3. It has also been shown that T cells from HIV-infected patients were even more sensitive to TRAIL induction of apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 25 publications
1
47
0
1
Order By: Relevance
“…Further, it has been demonstrated that TRAIL is up-regulated on the cell surface of HIVinfected or immune-activated macrophages (19,37). The function of TRAIL up-regulation during HIV-1 infection remains unclear, however, this process could mediate innate control of HIV-1 virus in MP as reservoirs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it has been demonstrated that TRAIL is up-regulated on the cell surface of HIVinfected or immune-activated macrophages (19,37). The function of TRAIL up-regulation during HIV-1 infection remains unclear, however, this process could mediate innate control of HIV-1 virus in MP as reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…The Ab against caspase-8 detects inactive form (55 kDa). The anti-caspase-9 Ab detects inactive form (48 kDa), and cleaved intermediate (37 Fig. 4).…”
Section: Inhibition Of Akt-1 Phosphorylation Sensitizes Mdm To Trail-mentioning
confidence: 99%
“…We hypothesize that virion production by CD4 ϩ T cells is efficient and rapid in the presence of HIV-infected LC and SEB, inducing apoptosis of infected T cells before significant proliferation can occur. HIV-infected LC may have produced pro-apoptotic factors in the presence of SEB, because HIV-infected APCs have previously been reported to produce pro-apoptotic factors, including TNF-␣ (20,21,25), Fas ligand (25), and TNF-related apoptosis-inducing ligand (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…First, the suppression of T cell proliferation could be due to Tat since it is known to play an important role in T cell apoptosis (32,33). The second possibility could be active suppression of the host-protective T cell response due to production of the counteractive disease promoting cytokines such as IL-10 and IL-4.…”
Section: Il-10 Produced By the Splenocytes Mediate The Suppressor Funmentioning
confidence: 99%